Relying on Research for Effective Response: A Survey Tool for Measuring the Impact of COVID-19 to Create Extension Resources - Lauri Baker; Ashley McLeod-Morin; Shelli Rampold; Anissa Zagonel; Ricky Telg; Angela Lindsey; Michaela Kandzer; Sandra Anderson; Sydney Honeycutt; Phillip Stokes; Valentina Castano; Alena Poulin (EDIS, 2022)
The UF/IFAS Center for Public Issues Education in Agriculture and Natural Resources (PIE Center) conducted a series of national public opinion surveys to examine the perceptions of Americans related to COVID-19. The PIE Center shared the survey data using Extension and outreach communication pieces, including issue guides, kinetic typography videos, webinars, and communication toolkits. Data collected from the PIE Center on Americans’ perceptions related to COVID-19 also informed two communication toolkits developed for Extension. This new 5-page article, published by the UF/IFAS Department of Agricultural Education and Communication, describes the instruments used to collect public opinion data related to COVID-19. Written by Lauri M. Baker, Ashley McLeod-Morin, Shelli Rampold, Anissa Zagonel, Ricky Telg, Angela B. Lindsey, Michaela Kandzer, Sandra Anderson, Sydney Honeycutt, Phillip Stokes, Valentina Castano, and Alena Poulin. https://edis.ifas.ufl.edu/wc426